Pengaruh Tri Kaya Parisudha Terhadap Indeks Kepuasan Masyarakat Layanan Pengujian Kendaraan Bermotor - Nyoman Sudarsana; I Nyoman Miarta Putra; Ni Nyoman Lisna Handayani (Jayapangus Press, 2026)
The element of service officer behavior in the Public Satisfaction Index of motor vehicle testing services needs specific attention when other service elements have reached the very good category. This study aims to analyze the effect of Tri Kaya Parisudha implementation on the Public Satisfaction Index, particularly the behavior element of service officers at the Department of Transportation of Buleleng Regency. The study uses a quantitative evaluative approach with a pre-post implementation design. Data were collected through questionnaires, observation, and service documents involving 200 service users and 20 service officers. The independent variable is Tri Kaya Parisudha, consisting of manacika, wacika, and kayika, while the dependent variable is the Public Satisfaction Index on the behavior element of service officers. Data were analyzed using descriptive statistics, Public Satisfaction Index conversion, comparative pre-post analysis, and simple regression. The results show that before implementation, the behavior element obtained an index value of 82.35 and was categorized as good, while the other service elements were categorized as very good. Regression analysis shows that Tri Kaya Parisudha has a positive contribution to service officer behavior and public satisfaction. The study concludes that Tri Kaya Parisudha can function as a local ethical framework to improve communication, responsibility, professionalism, and public satisfaction in culturally grounded public services.